The language of biotechnology : a dictionary of terms - Walker, John M. (ACS professional reference book, 1988)
This dictionary attempts to define routinely used specialized language in the various areas of biotechnology, and remain suitable for use by scientists involved in unrelated disciplines. Viewing biotechnology as the practical application of biological systems to the manufacturing and service industries, and to the management of the environment, terms defined have been selected from as broad a spectrum as possible to include work accomplished by the following disciplines: (1) microbiology; (2) pharmacology; (3) biochemistry; (4) chemistry; (5) physiology; (6) chemical engineering; (7) genetic engineering; (8) enzymology; and (9) cell biology. The typical biotechnologist can utilize this dictionary to integrate specialized work with studies being carried out by collaborators in related fields, particularly with respect to differences in terminology, i.e., jargon. (JJK)